A preliminary study on the effect of mentha cordifolia opiz. (yerba buena) crude extracts on HIV-1 replication in latently infected cells - Victoriano, Ann Florence B. (2003)
Mentha cordifolia Opiz., more popularly known in the Philippines as yerba buena has been shown to exhibit anti-microbial, antiviral and anti-inflammatory properties. This study was done to investigate its inhibitory effect on HIV-1 replication on HIV-1 latently infected cells (OM10.1). Crude hot water and protein extracts were prepared from pulverized yerba buena tablets. The protein extract was prepared from the hot water extract by ammonium sulfate precipitation. OM10.1 cells were pre-incubated with various concentrations of hot water and protein with various concentrations of hot water and protein extracts of yerba buena for 24-72 hours at 37 degrees C with 5% CO2. Culture supernatants were collected and tested for p24 antigen levels. The most potent inhibitory effect was found in the protein extract which reduced the HIV p24 expression level to 4.1% and 3.5% using 25 ug/ml and 100 ug/ml, after 24 and 48 hour stimulation with TNF-a, respectively. In OM10.1 cells without yerba buena extracts there was a 100% p24 antigen expression. The protein extract at these concentrations was likewise, non-cytotoxic to OM10.1 cells as determined by the MTT method. These results suggest that an anti-HIV activity maybe present in yerba buena, our very own variety of peppermint.
Thesis (MS Public Health, Medical Microbiology)--University of the Philippines, Manila
Keywords: Peppermint -- Therapeutic use; Medicinal plants; Mentha; Yerba buena